Improving the damping of vehicle vibration by improving pneumatic springs - Masliyev, Vyacheslav; Dushchenko, Vladislav; Yepifanov, Vitalii; Nanivskyi, Roman; Cherevko, Yurii; Masliev, Anton; Demydov, Alexander; Makarenko, Yurii (Eastern-European Journal of Enterprise Technologies, 2022)
It is known that the air suspension of vehicles, in which diaphragm-type air springs are used as an elastic element, do not provide the necessary vibration damping. The reason for this is that such air springs have a relatively large passive part. As a result, a relatively small mass of compressed air crosses through the throttle installed between the air spring and the additional reservoir. This mass of air contains thermal energy, into which the energy of vibrations, which enters through the walls of the additional reservoir into the environment, has turned. This is interpreted as vibration damping, which is insufficient due to the low air mass. Therefore, hydraulic vibration dampers are installed parallel to the diaphragm air springs, which complicates and increases the cost of the vehicle. Increasing the damping properties of such air suspensions could eliminate these hydraulic vibration dampers, which would reduce costs and simplify operation. An air suspension with an improved air spring has been proposed, which has an increased effective area and a reduced "passive" capacity, an empirical formula has been built to determine its damping coefficient, as well as an expression for the stiffness coefficient. Mathematical modeling of oscillations of vehicles with different designs of pneumatic springs was carried out in order to improve their damping. The mathematical model takes into account the change in the parameters of the air spring during vibrations. The study was carried out for the diesel train DL-02. Using mathematical modeling, the effectiveness of the air suspension with an improved air spring has been proven: its damping index reaches 0.263, and the vibration damping coefficient is 45,859 kg/s, which corresponds to the values ​​​​recommended for vehicles.